Мистическое учение Бхагавана Шри Раджниша (Ошо) - Жиртуева, Н.С. (Культура народов Причерноморья, 2014)
В статье исследуется учение представителя неоиндуизма Шри Раджниша (Ошо).
Делается вывод, что оно является синтезом идей имманентных (нетеистических) мистических
традиций мира. Абсолютом утверждается безличное Бытие-Сознание-Блаженство. Стремление к
объединению всех противоположностей определяет интеграционный характер учения, целью которого
является воспитание нового целостного человека. Уникальной является мистическая практика Ошо
Раджниша, объединяющая методы разных имманентных традиций мира. У статті досліджується вчення представника неоіндуїзму Шрі Раджніша (Ошо). Робиться
висновок, що воно постає синтезою ідей іманентних (нетеїстичних) містичних традицій світу.
Абсолютом проголошується безособове Буття-Свідомість-Блаженство. Прагнення до об’єднання усіх
протилежностей визначає інтеграційний характер вчення, метою якого є виховання нової цілісної
людини. Унікальною постає містична практика Ошо Раджніша, яка поєднує методи різних іманентних
традицій світу. The article deals with fundamental positions of the mystical study of the modern neohinduism, whose
representative is Bhagavan Sri Radžniša (Osho). The distinctive feature of the study is the desire to base the idea
of spiritual unity of mankind, the common origin of Eastern and Western religions. It comes to the conclusion
that this study is an original synthesis of ideas in immanent (non-theistic) mystical traditions of the world,
denying the existence of the over-world the Creator. The Absolute is an impersonal Being-Consciousness-Bliss,
to which a mystic strives for merging. The aim of Osho study considers teaching a new man who overcame the
chaos of internal contradictions and achieved global integrity. The aspiration for uniting all of the oppositesbetween
East and West, male and female, matter and consciousness, prayer and meditation-defines the nature of
the study. The mystic Osho Radžniša practice is unique that combines the methods of various traditions of the
world: psychosomatic practice of Tantrism, dynamic and passive meditation practice of Hinduism and
Buddhism, love-return of the Hindu Bhakti. In the mystical practice of Osho there isn’t a method of disciplinary
asceticism, that approves antiascetic direction of the study.